Identification of Tampered SMS Messages in iPhone – A Case Study - Chunduru, Eswara Sai Prasad; Mangarai, Krishna; Babu, Subrahmani; Pathak, Manohar B (International Journal of Computer Sciences and Engineering, 2019)
Mobile Phones, now-a-days have become the primary source of evidence in any type of investigation for providing initial leads for framing the future investigation as well as primary evidence. The retrieval and analysis of SMS messages, including deleted ones from the memory of smart mobiles is one of the main process of mobile phone forensics. With the evolution of technology, criminals can manipulate the SMS database and tamper the messages to prove their virtue and mis-guide the investigation. In the current paper we have discussed the method adopted for proving the authenticity of SMS messages retrieved during the analysis of an iPhone.